A novel framework for spatial normalization of dose distributions in voxel-based analyses of brain irradiation outcomes. (January 2020) - Monti, S.; Paganelli, C.; Buizza, G.; Preda, L.; Valvo, F.; Baroni, G.; Palma, G.; Cella, L.
Highlights: A new spatial normalization framework for brain dose distributions is proposed. The proposed framework is based on the combined use of MR and planning CT images. A formal criterion for non-acceptable normalization is provided. The devised framework is robust and paves the way for future brain toxicity studies. Abstract: Purpose: To devise a novel Spatial Normalization framework for Voxel-based analysis (VBA) in brain radiotherapy. VBAs rely on accurate spatial normalization of different patients' planning CTs on a common coordinate system (CCS). The cerebral anatomy, well characterized by MRI, shows instead poor contrast in CT, resulting in potential inaccuracies in VBAs based on CT alone. Methods: We analyzed 50 meningioma patients treated with proton-therapy, undergoing planning CT and T1-weighted (T1w) MRI. The spatial normalization pipeline based on MR and CT images consisted in: intra-patient registration of CT to T1w, inter-patient registration of T1w to MNI space chosen as CCS, doses propagation to MNI. The registration quality was compared with that obtained by Statistical Parametric Mapping software (SPM), used as benchmark. To evaluate the accuracy of dose normalization, the dose organ overlap (DOO) score was computed on gray matter, white matter and cerebrospinal fluid before and after normalization. In addition, the trends in the DOOs distribution were investigated by means of cluster analysis. Results: The registration quality was higher for the proposed method compared to SPM ( p < 0.001). The DOO scores showed a significant improvement after normalization ( p < 0.001). The cluster analysis highlighted 2 clusters, with one of them including the majority of data and exhibiting acceptable DOOs. Conclusions: Our study presents a robust tool for spatial normalization, specifically tailored for brain dose VBAs. Furthermore, the cluster analysis provides a formal criterion for patient exclusion in case of non-acceptable normalization results. The implemented framework lays the groundwork for future reliable VBAs in brain irradiation studies.